Respuesta :
Set the first number as x.
Note that three consecutive integers are 3 numbers that are 1 greater than the previous.
(x) + (x + 1) + (x + 2) = 72
Simplify. Combine like terms
3x + 3 = 72
Isolate the x. Note the equal sign. What you do to one side, you do to the other. Do the opposite of PEMDAS. First, subtract 3 from both sides
3x + 3 (-3) = 72 (-3)
3x = 69
Next, divide 3 from both sides
3x/3 = 69/3
x = 23
------------------------------------------------------------------------------------------------------------------------
23 is your first answer
Plug in 23 for each x.
------------------------------------------------------------------------------------------------------------------------
(x) + (x + 1) + (x + 2) = 72
(x) = 23
(x + 1) = 23 + 1 = 24
(x + 2) = 23 + 2 = 25
23, 24, 25 are your answers
------------------------------------------------------------------------------------------------------------------------
~Rise Above the Ordinary
Answer:
Three consecutive integers have a sum of 72.
So They will: x, x+1, x+2
x + (x +1) + (x+ 2) = 72
= 3x + 3 = 72
= 3x = 72 - 3
= 3x = 69
= x = 33
By putting value of x in: x, x+1, x+2
Hence the integers will be: 33, 34,35